Gold(I)/chiral brønsted acid catalyzed enantioselective hydroamination-hydroarylation of alkynes: effect of remote hydroxyl group in the reactivity and enantioselectivity - Shinde, Valmik S.; Mane, Manoj V.; Vanka, Kumar; Mallick, Arijit; Patil, Nitin T. (Chemistry - A European Journal, 2015)

Gold-catalyzed cycloisomerization of pyridine-bridged 1,8-Diynes: An expedient access to luminescent cycl[3.2.2]azines - Chintawar, Chetan C.; Mane, Manoj V.; Tathe, Akash G.; Biswas, Suprakash; Patil, Nitin T. (Organic Letters, 2019)
Gold-catalyzed diyne cycloisomerizations involving carbene/alkyne metathesis have been the focal point of attention for the past few years as it offers great potential to build complex polycyclic architectures. However, the design of novel cycloisomerizations has been mostly limited to 1,5/1,6-diynes and has remained very challenging to apply for higher 1,n-diynes. Herein, we disclose an unprecedented cycloisomerization of pyridine-bridged 1,8-diynes involving carbene/alkyne metathesis to access luminescent cycl[3.2.2]azines.

Gold(I)-catalyzed hydroxy group assisted C(sp(2))-H alkylation of enaminones with diazo compounds to access 3-alkyl chromones - Bagle, Pradip N.; Mane, Manoj V.; Sancheti, Shashank P.; Gade, Amol B.; Shaikh, Samir R.; Baik, Mu-Hyun; Patil, Nitin T. (Organic Letters, 2019)
A strategy for expedient synthesis of 3-substituted chromones from easily available o-hydroxyarylenaminones and diazo compounds has been developed. Carefully conducted experimental and computational studies led us to propose an uncommon mechanistic pathway involving the hydroxyl group assisted alkylation of enaminones with in situ generated gold carbenes.